THE INFLUENCE OF CONSUMERS, EMPLOYEES, MEDIA AND SHAREHOLDERS’ ENGAGEMENT ON THE QUALITY OF SUSTAINABILITY REPORTING IN INDONESIA - Nisa, Siti Ammara Fazilatun (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study delves into the nuanced variables of sustainability reporting quality within the context of energy, basic materials, industrial, consumer non-cyclicals, consumer cyclicals, as well as transportation and logistics sectors. Employing a content analysis on companies’ reports, this research scrutinizes the depth and breadth of consumer, employee, media, and shareholders’ engagement on the quality sustainability reporting of companies listed on the IDX from the period of 2019-2022. In pursuit of these objectives, a quantitative study approach was employed. The research design encompasses content analysis to examine the quality of sustainability reporting from a representative sample of 45 organizations within the energy, basic materials, industrial, consumer non-cyclicals, consumer cyclicals, as well as transportation and logistics sectors. Additionally, in this research, the Multiple Logistic Regression analysis was used. The research findings underscore four key aspects; in regards to the hypotheses tested. All four variables- consumer, employee, media, and shareholders’ engagement- emerged as critical determinants impacting the quality of sustainability reporting. These findings contribute to the existing body of knowledge by offering practical implications for organizations aiming to elevate their sustainability reporting quality, thereby fostering a more transparent and responsible business environment.